2018
DOI: 10.1159/000488712
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Pathology of Myelodysplastic Syndrome

Abstract: The diagnosis and classification of myelodysplastic syndromes (MDS) are based on cytomorphology and cytogenetics (WHO classification). Prognosis is best defined by the Revised International Prognostic Scoring System (IPSS-R). In recent years, an increasing number of molecular aberrations have been discovered. They are already included in the classification (e.g., SF3B1) and, more importantly, have emerged as valuable markers for better classification, particularly for defining risk groups. Mutations in genes s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 22 publications
0
29
0
4
Order By: Relevance
“…The present study demonstrated its usefulness in MDS, a group of heterogeneous neoplasias gaining various genetic alterations due to genetic instability, whose causes of initiation are not completely understood (47,48). The incidence is four to five out of 100,000 people per year and .30 out of 100,000 are over the age of 70 (49). The disease is staged by blood cell counts, bone marrow blast percentages, and cytogenetic results, leading to the calculation of the IPSS-R as a prognostic parameter (28).…”
Section: Discussionmentioning
confidence: 61%
“…The present study demonstrated its usefulness in MDS, a group of heterogeneous neoplasias gaining various genetic alterations due to genetic instability, whose causes of initiation are not completely understood (47,48). The incidence is four to five out of 100,000 people per year and .30 out of 100,000 are over the age of 70 (49). The disease is staged by blood cell counts, bone marrow blast percentages, and cytogenetic results, leading to the calculation of the IPSS-R as a prognostic parameter (28).…”
Section: Discussionmentioning
confidence: 61%
“…Although many therapeutic strategies have been employed, the disease remains incurable [2,3]. e pathophysiology of MDS involves epigenetic, genetic, and cytogenetic aberrations [4]. Aberrant DNA methylation plays a key role in MDS.…”
Section: Introductionmentioning
confidence: 99%
“…Miyelodisplastik sendrom (MDS) yetersiz ve displastik hematopoez ile karakterize, klonal bir hematolojik hastalıktır. Kemik iliğinde hiperselülarite ve blast hücre artışı olmasına karşın, perifer kanında sitopeni gözlenir (1). MDS'li hastaların klinik fenotipi çok çeşitlidir.…”
Section: Introductionunclassified